Application Of The Make A Match Type Cooperatif Learning Model In Improving Arts And Culture Learning Outcomes For SMPN 07 Woja Students - Adiprasetio Prabowo; Swandi Swandi; Aidin Aidin (Universitas Maritim AMNI Semarang, 2024)
The results of this research are descriptive efforts to improve arts and culture learning outcomes by using the make a match type cooperative learning model for class VII students at SMPN 07 Woja. This research uses a classroom action research (PTK) design. Implementation of PTK actions is carried out in several periods or cycles. The data collection methods used include the observation method, listening method, questionnaire method and documentation method. Based on the research results, it shows that there is an increase in arts and culture learning outcomes using the make a match learning model for class VII students at SMPN 07 Woja which occurs starting from pre-action, cycle I and cycle II. The pre-action results showed that the average score reached 68.10 and was at a percentage of 34.48%. After taking action in cycle I, the average score increased to 77.06 and was included in the criteria of 68.96%. In cycle II the average arts and culture score increased again to 81.29, which is in the very good criteria with a percentage of 82.75%. This shows that the use of the make a match learning model carried out in each cycle was successful in achieving the expected success indicators.